Effect of probiotics at different intervention time on glycemic control in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Wang, Xinghui; Chen, Lu; Zhang, Chunling; Shi, Qing; Zhu, Lei; Zhao, Sisi; Luo, Zhiqin; Long, Yirun (Frontiers in Endocrinology, 2024)
Background: Type 2 diabetes mellitus(T2DM) is characterized by hyperglycemia. Gut microbiome adjustment plays a positive part in glucose regulation, which has become a hotspot. Probiotics have been studied for their potential to control the gut flora and to treat T2DM. However, the conclusion of its glucose-lowering effect is inconsistent based on different probiotic intervention times.To comprehensively evaluate how various probiotic intervention times affect glycemic control in people with T2DM.We retrieved PubMed, Embase, Web of Science, and Cochrane Library on randomized controlled trials(RCTs)regarding the impact of probiotics on glycemic control in patients with T2DM from the inception to November 16, 2023. Separately, two researchers conducted a literature analysis, data extraction, and bias risk assessment of the involved studies. We followed the PRISMA guidelines, used RevMan 5.4 software for meta-analysis, and assessed the risk of bias by applying the Cochrane Handbook for Systematic Reviews 5.1.0.We included eight RCTs with 507 patients. Meta-analysis revealed that the use of probiotics might considerably reduce levels of glycosylated hemoglobin (HbA1c) mean deviation (MD) =-0.33, 95% confidence interval (CI) (-0.59, -0.07), p = 0.01 and Insulin standard mean deviation (SMD) = -0.48, 95% CI (-0.74, -0.22), p = 0.0003 Homeostatic Model Assessment for Insulin Resistance (HOMA-IR)SMD = -1.36, 95% CI (-2.30, -0.41), p = 0.005 than placebo group. No statistically significant differences were found regarding fasting blood glucose (FBG) and body mass index (BMI) SMD = -0.39, 95% CI (-0.83, 0.05), p = 0.08, SMD = -0.40, 95% CI (-1.07, 0.27), p = 0.25, respectively. Subgroup analyses, grouped by intervention times, showed that six to eight weeks of intervention improved HbA1c compared to the control group (p  0.05), both six to eight weeks and 12-24 weeks had a better intervention effect on Insulin, and HOMA-IR (p  0.05).In contrast, no statistically significant variation were found between FBG and BMI regarding duration.This meta-analysis found probiotics at different intervention times play a positive role in modulating glucose in T2DM, specifically for HbA1c in six to eight weeks, Insulin and HOMA-IR in six to eight weeks, and 12-24 weeks. To confirm our findings, further large-sample research is still required.